The Benefits, Challenges and Impacts of Telehealth Student Clinical Placements for Accredited Health Programs During the COVID-19 Pandemic - Bacon, Rachel; Hopkins, Sian; Kellett, Jane; Millar, CaraJane; Smillie, Linda; Sutherland, Rebecca (Frontiers in Medicine, 2022)
Introduction: Despite the advantages of telehealth, there has been a reluctance in its widespread adoption. During the COVID-19 pandemic, telehealth services and related placements increased internationally. Yet, there is currently limited research on the use of telehealth for student clinical placements. Aim: To explore the perceived benefits, challenges, and impacts of telehealth placements for key stakeholders (clients, students, clinical educators, and placement co-ordinators) in allied health courses. Methods: Stakeholder experiences with telehealth placements, undertaken within an Australian Allied Health University Clinic, were explored in virtual focus groups held between November 2020 and March 2021. These discussions used semi-structured interview questions, were audiotaped and transcribed verbatim. They were then thematically analysed independently by two researchers, then cross-checked for consistency, using a qualitative descriptive approach, with reflexivity applied. Results: Twenty-six stakeholders from six allied health disciplines participated in seven homogeneous focus groups. Three themes were identified: (1) telehealth placements support competency development and graduate employability; (2) telehealth placements enable students to provide person centred-care; and (3) telehealth placements enabled innovation. Conclusion: Telehealth placements can make a valuable contribution as part of an overall placement program within accredited health courses and offer distinct advantages to student learning outcomes.